The delay in the first lift from vessel alongside and the effect on overall vessel gross productivity - Navinder Murugiah, 1978-; Muhammad Zaly Shah Muhammad Hussein; Fakulti Alam Bina (2009)
Thesis (Sarjana Sains (Perancangan dan Pengangkutan)) - Universiti Teknologi Malaysia, 2009